14.9k views
2 votes
H(x)=x2+1 k(x)=x-2
(h-k)(3)

1 Answer

4 votes

Answer:

(h-k)(3) = 9

Explanation:

h(x) = x² + 1

k(x) = x - 2

To find (h-k)(3) we must first find (h - k)(x)

To find (h - k)(x) subtract k(x) from h(x)

That's

(h - k)(x) = x² + 1 - ( x - 2)

(h - k)(x) = x² + 1 - x + 2

(h - k)(x) = x² - x + 1 + 2

We have

(h - k)(x) = x² - x + 3

To find (h-k)(3) substitute the value of x that's 3 into (h - k)(x) that's replace every x in (h - k)(x) by 3

We have

(h-k)(3) = (3)² - 3 + 3

= 9 - 3 + 3

= 9 - 0

We have the final answer as

(h-k)(3) = 9

Hope this helps you

User Aleksandar G
by
5.2k points